Moisturizing composite kraft paper

By adopting a three-layer structure moisturizing composite kraft paper, combining the combination of PEAT and PLA, the addition of nanofillers and the modification of thermoplastic polyurethane, the multiple problems of kraft paper in practical applications are solved, and better waterproof, breathable and mechanical are achieved. Performance and environmentally friendly performance.

CN119465700AActive Publication Date: 2025-02-18DONGGUAN BRIGHT PACKAGING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411619837.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

In actual applications, kraft paper has insufficient waterproof performance, insufficient oilproof performance, unstable mechanical performance, environmental protection and food safety problems, insufficient weather resistance and breathability problems.

Method used

Moisturizing composite kraft paper with three-layer structure, the outer layer is kraft paper, the middle layer is a modified adhesive layer, and the inner layer is a modified PBAT film. The performance of the adhesive layer is improved by combining PEAT with PLA and polylactic acid copolymer, nanofillers are added, and thermoplastic polyurethane is modified.

Benefits of technology

It significantly improves the waterproof performance and breathability of kraft paper, improves the waterproof effect at high temperatures, enhances mechanical properties and tensile strength, and improves environmental protection and food safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005133155020000091
    Figure BDA0005133155020000091
  • Figure BDA0005133155020000101
    Figure BDA0005133155020000101
Patent Text Reader

Abstract

The invention belongs to the technical field of kraft paper, and particularly relates to moisturizing composite kraft paper. The moisturizing composite kraft paper comprises an outer layer, a middle layer and an inner layer, the outer layer is made of kraft paper, and the middle layer is a bonding layer; the inner layer is a modified PBAT film; the preparation method of the modified PBAT film comprises the following steps: mixing 80-85 parts by weight of PBAT, 7-12 parts by weight of PLA, 15-20 parts by weight of a polylactic acid-glycolic acid copolymer and 0.7-1 part by weight of an anti-hydrolysis agent, heating to 220-230 DEG C, stirring at a stirring speed of 80-90 r / min for 2-3 h, continuously adding 5-8 parts by weight of a nano filler, and carrying out ultrasonic dispersion for 15-20 min to obtain a mixture, and adding the mixture into a cast film machine, carrying out casting to obtain a cast film, and calendering the cast film by adopting a water-cooling calendering roller with the surface temperature of 20-25 DEG C to obtain the modified PBAT film. The prepared moisturizing composite kraft paper is good in waterproof, breathable and oil-proof effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of kraft paper, and in particular relates to a moisture-retaining composite kraft paper. Background Art

[0002] Kraft paper is a common paper material, known for its durability, tear resistance and good waterproof performance. As an economical, practical and environmentally friendly paper material, kraft paper is widely used in packaging, printing, writing and other fields.

[0003] Kraft paper is widely used in the production of food bags, handbags and other packaging materials due to its high strength, tear resistance and environmental protection characteristics. However, in practical applications, it still faces some technical problems: 1. Insufficient waterproof performance. Kraft paper has strong natural water absorption and is easily affected by moisture, which affects its mechanical properties and appearance. 2. Insufficient oil resistance. Kraft paper is easily penetrated by grease, which affects its performance, especially in food packaging. 3. Unstable mechanical properties. The mechanical properties of kraft paper will decrease in humid or high temperature environments. 4. Environmental protection and food safety issues. The production process of kraft paper and the coating materials used may contain harmful substances, which affect environmental protection and food safety. 5. Insufficient weather resistance. When used outdoors, kraft paper is easily affected by ultraviolet rays, temperature changes and other factors, resulting in performance degradation. 6. Air permeability issues. The air permeability of kraft paper may cause food to deteriorate, especially in situations where sealed packaging is required.

[0004] The prior art uses kraft paper to make composite films to improve the water resistance of kraft paper. For example, kraft paper is composited with polyethylene film to form a waterproof barrier. This method can significantly improve the waterproof performance of kraft paper while maintaining its mechanical strength. Similarly, the use of polypropylene film composited with kraft paper can also provide good waterproof performance. However, these materials have poor degradability and are not in line with the concept of environmental protection. At the same time, the air permeability of kraft paper is not ideal and cannot meet the needs of the existing market. Therefore, a moisturizing composite kraft paper is urgently needed. Summary of the invention

[0005] The purpose of the invention is to provide a moisturizing composite kraft paper, which has good air permeability and waterproofness, is breathable and water-proof, and has a good moisturizing effect.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A moisturizing composite kraft paper, comprising an outer layer, a middle layer and an inner layer; the outer layer is made of kraft paper, the middle layer is an adhesive layer; the inner layer is a modified PBAT film; the outer layer has a thickness of 20-25 μm, the inner layer has a thickness of 10-15 μm, and the middle layer has a thickness of 15-20 μm;

[0008] The preparation method of the modified PBAT film comprises the following steps: by weight, 80-85 parts of PBAT, 7-12 parts of PLA, 15-20 parts of polylactic acid-glycolic acid copolymer and 0.7-1 part of anti-hydrolysis agent are mixed, the temperature is raised to 220-230° C., the stirring speed is 80-90 r / min, the stirring reaction time is 2-3 hours, 5-8 parts of nano fillers are continuously added, ultrasonic dispersion is performed for 15-20 minutes to obtain a mixture, the mixture is added to a cast film machine, cast to obtain a cast film, and calendered using a water-cooled calendering roller with a surface temperature of 20-25° C. to obtain a modified PBAT film.

[0009] Furthermore, the anti-hydrolysis agent is bis(2,6-diisopropylphenyl)carbodiimide.

[0010] Furthermore, the nano filler comprises nano calcium carbonate, nano zinc oxide and nano lanthanum oxide in a weight ratio of 1: (1.2-1.5): (0.6-0.8).

[0011] Furthermore, the particle size of the nano calcium carbonate is 15nm-25nm, and the specific surface area is 30-60m 2 / g, the particle size of nano lanthanum oxide is 30nm-50nm, and the specific surface area is 15-30m 2 / g. The particle size of nano lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g.

[0012] PBAT has good degradability and is beneficial to environmental protection. The present invention attempts to compound it with kraft paper to improve the waterproofness of the composite kraft paper, but the waterproof effect at high temperature is not ideal. The present invention compounds PEAT with PLA and polylactic acid-glycolic acid copolymer to improve the waterproof performance of kraft paper at high temperatures. Analysis shows that PLA and PLGA have high surface hydrophobicity, which can improve the waterproof performance of composite kraft paper. At the same time, the flexibility and ductility of PBAT can be combined with the rigidity and strength of PLA to improve the mechanical properties of the composite material.

[0013] At the same time, adding nanofillers can improve the air permeability of kraft paper. Nanofillers can form a microporous structure in the composite material, providing a channel for gas molecules to pass through. Nanofillers can improve the interface compatibility between PBAT, PLA and PLGA to form a more uniform composite material. Good interface compatibility can reduce defects inside the material and improve air permeability.

[0014] Furthermore, the method for preparing the adhesive layer comprises the following steps: by weight,

[0015] (1) 15-20 parts of brominated butyl rubber are plasticized at 170-180° C. for 5-10 minutes, and then 0.3-0.5 parts of silane coupling agent KH550, 2-4 parts of magnesium stearate, and 100 parts of thermoplastic polyurethane A are added, and the mixture is mixed for 15-20 minutes, and then crushed at room temperature to obtain a modified thermoplastic polyurethane;

[0016] (2) 10-14 parts of thermoplastic polyurethane B, 20-25 parts of modified thermoplastic polyurethane, 0.04-0.07 parts of ultraviolet absorber and 0.02-0.05 parts of antioxidant are mixed, and cast by a single screw extruder to obtain a cast film, which is then calendered by a water-cooled calendering roller with a surface temperature of 20-25° C. to obtain an adhesive layer.

[0017] The tensile strength of the composite kraft paper is not ideal when the commercially available adhesive material is used for bonding. The analysis shows that the commercially available adhesive material may not be compatible with the kraft paper or PBAT layer. The commercially available adhesive material may not be compatible with the kraft paper or PBAT layer. The present invention modifies thermoplastic polyurethane A with brominated butyl rubber, and then compounds it with thermoplastic polyurethane B to improve the tensile strength of the composite kraft paper. At the same time, the texture of the composite kraft paper is improved. This is mainly because brominated butyl rubber has excellent elasticity and toughness, which can significantly improve the impact strength and tear resistance of thermoplastic polyurethane A, form an energy dissipation zone in the stress concentration area, reduce the expansion of cracks, and improve tensile strength; modified thermoplastic polyurethane and thermoplastic polyurethane B have different physical and chemical properties, and can achieve complementary performance through compounding, which can simultaneously improve the tensile strength and elasticity of the composite material. Bromobutyl rubber has good softness and elasticity, which can improve the touch of the composite material; the surface smoothness of the composite adhesive layer is higher through the material compounding, which reduces the roughness of the surface and makes the surface of the composite kraft paper more delicate.

[0018] Furthermore, the thermoplastic polyurethane A is a thermoplastic polyurethane with a model number of 9670A. Brand: Bayer, Germany.

[0019] Furthermore, the thermoplastic polyurethane B is a thermoplastic polyurethane with a model number of 9370AU and a brand of Bayer, Germany.

[0020] Bromobutyl rubber, model: EXXPRO TM 3433, Brand: Exxon, USA.

[0021] Furthermore, the temperature of the barrel section 1 of the single-screw extruder is 100-105°C, the temperature of the section 2 is 130-135°C, the temperature of the section 3 is 145-150°C, the temperature of the section 4 is 160-165°C, and the temperature of the section 5 is 150-155°C.

[0022] Furthermore, the preparation method of the moisturizing composite kraft paper comprises the following steps: placing the outer layer, the middle layer and the inner layer on a hot roller press in order, stacking them from top to bottom, and hot roller pressing and laminating them to obtain the moisturizing composite kraft paper.

[0023] Furthermore, the rolling temperature is 130-135°C and the pressure is 4.5-5kg / cm 2 .

[0024] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0025] 1. The present invention compounds PEAT with PLA and polylactic acid-glycolic acid copolymer to improve the waterproof performance of kraft paper at high temperatures.

[0026] 2. Adding nanofillers to the modified PBAT membrane can improve the air permeability of kraft paper.

[0027] 3. The present invention modifies thermoplastic polyurethane A with brominated butyl rubber and then compounds it with thermoplastic polyurethane B to improve the tensile strength of the composite kraft paper and the texture of the composite kraft paper. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The raw materials used in the following examples of the present invention are all commercially available products:

[0030] Kraft paper, maple leaf refined kraft paper, No.: 205B-50, weight 40-80g.

[0031] PBAT, Shanghai Yiding Plastic Co., Ltd., brand: TH801T.

[0032] PLA, NatureWorks, USA, model: 4060D.

[0033] Poly(lactic acid-glycolic acid copolymer), Suzhou Renfu Plastic Co., Ltd., brand JJ901.

[0034] UV absorber, BASF, UV absorber 234.

[0035] Antioxidant, BASF, Antioxidant 1010.

[0036] Example 1

[0037] The present embodiment provides a moisturizing composite kraft paper, comprising an outer layer, a middle layer and an inner layer; the outer layer is made of kraft paper, the middle layer is an adhesive layer; the inner layer is a modified PBAT film; the thickness of the outer layer is 22 μm, the thickness of the inner layer is 12 μm, and the thickness of the middle layer is 18 μm.

[0038] The preparation method of the modified PBAT film comprises the following steps: by weight, 82 parts of PBAT, 10 parts of PLA, 17 parts of polylactic acid-glycolic acid copolymer and 0.8 parts of anti-hydrolysis agent are mixed, the temperature is raised to 225° C., the stirring speed is 85 r / min, the stirring reaction time is 2.5 hours, 7 parts of nano filler are continuously added, ultrasonic dispersion is performed for 18 minutes to obtain a mixture, the mixture is added to a cast film machine, cast to obtain a cast film, and calendered using a water-cooled calendering roller with a surface temperature of 22° C. to obtain a modified PBAT film.

[0039] The anti-hydrolysis agent is bis(2,6-diisopropylphenyl)carbodiimide.

[0040] The nano filler comprises nano calcium carbonate, nano zinc oxide and nano lanthanum oxide in a weight ratio of 1:1.4:0.7. The particle size of the nano calcium carbonate is 15nm-25nm, and the specific surface area is 30-60m 2 / g, the particle size of nano lanthanum oxide is 30nm-50nm, and the specific surface area is 15-30m 2 / g. The particle size of nano lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g.

[0041] The preparation method of the adhesive layer comprises the following steps: by weight,

[0042] (1) 17 parts of brominated butyl rubber were plasticized at 175° C. for 8 minutes, and then 0.4 parts of silane coupling agent KH550, 3 parts of magnesium stearate, and 100 parts of thermoplastic polyurethane A were added, and the mixture was mixed for 18 minutes, and then crushed at room temperature to obtain a modified thermoplastic polyurethane;

[0043] (2) 12 parts of thermoplastic polyurethane B, 22 parts of modified thermoplastic polyurethane, 0.06 parts of ultraviolet absorber and 0.04 parts of antioxidant are mixed, and a single-screw extruder is used. The temperature of the barrel of the single-screw extruder is 102° C. for section 1, 133° C. for section 2, 147° C. for section 3, 162° C. for section 4 and 152° C. for section 5. The cast film is then cast using a water-cooled calendering roller with a surface temperature of 22° C. to obtain an adhesive layer.

[0044] Thermoplastic polyurethane A is a thermoplastic polyurethane with a model number of 9670A. Brand: Bayer, Germany. Thermoplastic polyurethane B is a thermoplastic polyurethane with a model number of 9370AU. Brand: Bayer, Germany. Bromobutyl rubber, model number: EXXPROTM 3433, Brand: Exxon, USA.

[0045] The preparation method of the moisturizing composite kraft paper comprises the following steps: placing the outer layer, the middle layer and the inner layer on a hot roller press in order, stacking them from top to bottom, and hot roller pressing them together, with the roller pressing temperature being 132° C. and the pressure being 4.7 kg / cm 2 , and obtain moisturizing composite kraft paper.

[0046] Example 2

[0047] The present embodiment provides a moisturizing composite kraft paper, comprising an outer layer, a middle layer and an inner layer; the outer layer is made of kraft paper, the middle layer is an adhesive layer; the inner layer is a modified PBAT film; the thickness of the outer layer is 22 μm, the thickness of the inner layer is 12 μm, and the thickness of the middle layer is 18 μm.

[0048] The preparation method of the modified PBAT film comprises the following steps: by weight, 80 parts of PBAT, 12 parts of PLA, 15 parts of polylactic acid-glycolic acid copolymer and 1 part of anti-hydrolysis agent are mixed, the temperature is raised to 220° C., the stirring speed is 90 r / min, the stirring reaction time is 2 hours, 8 parts of nano fillers are continuously added, ultrasonic dispersion is performed for 15 minutes to obtain a mixture, the mixture is added to a cast film machine, cast to obtain a cast film, and calendered using a water-cooled calendering roller with a surface temperature of 25° C. to obtain a modified PBAT film.

[0049] The anti-hydrolysis agent is bis(2,6-diisopropylphenyl)carbodiimide.

[0050] The nano filler comprises nano calcium carbonate, nano zinc oxide and nano lanthanum oxide in a weight ratio of 1:1.2:0.8. The particle size of the nano calcium carbonate is 15nm-25nm, and the specific surface area is 30-60m 2 / g, the particle size of nano lanthanum oxide is 30nm-50nm, and the specific surface area is 15-30m 2 / g. The particle size of nano lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g.

[0051] The preparation method of the adhesive layer comprises the following steps: by weight,

[0052] (1) 15 parts of brominated butyl rubber were plasticized at 180° C. for 10 minutes, and then 0.5 parts of silane coupling agent KH550, 2 parts of magnesium stearate, and 100 parts of thermoplastic polyurethane A were added, and the mixture was mixed for 20 minutes, and then crushed at room temperature to obtain a modified thermoplastic polyurethane;

[0053] (2) 10 parts of thermoplastic polyurethane B, 25 parts of modified thermoplastic polyurethane, 0.04 parts of ultraviolet absorber and 0.05 parts of antioxidant are mixed, and a single-screw extruder is used. The temperature of the barrel of the single-screw extruder is 105° C. for section 1, 130° C. for section 2, 150° C. for section 3, 160° C. for section 4 and 155° C. for section 5. The mixture is cast to obtain a cast film, and a water-cooled calendering roller with a surface temperature of 20° C. is used for calendering to obtain an adhesive layer.

[0054] Thermoplastic polyurethane A is a thermoplastic polyurethane with a model number of 9670A. Brand: Bayer, Germany. Thermoplastic polyurethane B is a thermoplastic polyurethane with a model number of 9370AU. Brand: Bayer, Germany. Bromobutyl rubber, model number: EXXPRO TM 3433, Brand: Exxon, USA.

[0055] The preparation method of the moisturizing composite kraft paper comprises the following steps: placing the outer layer, the middle layer and the inner layer on a hot roller press in order, stacking them from top to bottom, and hot roller pressing them together, with the roller pressing temperature being 135° C. and the pressure being 4.5 kg / cm 2 , and obtain moisturizing composite kraft paper.

[0056] Comparative Example 1

[0057] The difference between this comparative example and Example 1 is that the preparation method of the modified PBAT film comprises the following steps: by weight, 78 parts of PBAT, 20 parts of PLA, 11 parts of polylactic acid-glycolic acid copolymer and 0.8 parts of anti-hydrolysis agent are mixed, the temperature is raised to 225° C., the stirring speed is 85 r / min, the stirring reaction time is 2.5 h, 7 parts of nanofiller are continuously added, ultrasonic dispersion is performed for 18 min to obtain a mixture, the mixture is added to a cast film machine, cast to obtain a cast film, and calendered using a water-cooled calendering roller with a surface temperature of 22° C. to obtain a modified PBAT film.

[0058] Comparative Example 2

[0059] The difference between this comparative example and Example 1 is that the nano filler includes nano calcium carbonate, nano zinc oxide and nano lanthanum oxide in a weight ratio of 1:1:1.

[0060] Comparative Example 3

[0061] The difference between this comparative example and Example 1 is that the particle size of the nano calcium carbonate is 40nm-55nm, and the specific surface area is 10-20m 2 / g, the particle size of nano lanthanum oxide is 60nm-80nm, and the specific surface area is 5-10m 2 / g. The particle size of nano lanthanum oxide is 70nm-90nm, and the specific surface area is 5-10m 2 / g.

[0062] Comparative Example 4

[0063] The difference between this comparative example and Example 1 is that the preparation method of the adhesive layer comprises the following steps: by weight,

[0064] (1) 17 parts of brominated butyl rubber were plasticized at 175° C. for 8 minutes, and then 0.4 parts of silane coupling agent KH550, 3 parts of magnesium stearate, and 100 parts of thermoplastic polyurethane A were added, and the mixture was mixed for 18 minutes, and then crushed at room temperature to obtain a modified thermoplastic polyurethane;

[0065] (2) 17 parts of thermoplastic polyurethane B, 17 parts of modified thermoplastic polyurethane, 0.06 parts of ultraviolet absorber and 0.04 parts of antioxidant are mixed, and a single-screw extruder is used. The temperature of the barrel of the single-screw extruder is 102° C. for section 1, 133° C. for section 2, 147° C. for section 3, 162° C. for section 4 and 152° C. for section 5. The cast film is then cast using a water-cooled calendering roller with a surface temperature of 22° C. to obtain an adhesive layer.

[0066] Comparative Example 5

[0067] The difference between this comparative example and Example 1 is that the preparation method of the bonding layer comprises the following steps: 12 parts of thermoplastic polyurethane B, 22 parts of thermoplastic polyurethane A, 0.06 parts of ultraviolet absorber and 0.04 parts of antioxidant are mixed by weight, and a single-screw extruder is used, and the temperature of the barrel section 1 of the single-screw extruder is 102°C, the temperature of the barrel section 2 is 133°C, the temperature of the barrel section 3 is 147°C, the temperature of the barrel section 4 is 162°C, and the temperature of the barrel section 5 is 152°C. Casting obtains a cast film, and calendering is performed using a water-cooled calendering roller with a surface temperature of 22°C to obtain a bonding layer.

[0068] Comparative Example 6

[0069] The difference between this comparative example and Example 1 is that the thermoplastic polyurethane A is a thermoplastic polyurethane of model 9370AU, brand: Bayer, Germany. The thermoplastic polyurethane B is a thermoplastic polyurethane of model 9670A, brand: Bayer, Germany.

[0070] Performance Testing

[0071] The composite kraft papers prepared in Examples 1-2 and Comparative Example 106 were subjected to performance tests.

[0072] Mechanical properties test: tensile strength is tested according to national standard GB / T1040.3-2006.

[0073] Barrier performance: Oxygen transmission rate [cm3 / (m2.d.atm0)] was tested according to the national standard GB / T1038-2000.

[0074] Waterproof performance: The composite kraft paper is quickly heat-sealed through an air cushion machine, and then placed in water and allowed to stand for 30 minutes. The water tank is evacuated to observe the air leakage of the air cushion, and the vacuum degree is -30kpa. The specific test conditions are: bag making specification 200*100mm, inflator air volume 28L / min, heat sealing temperature 200℃, speed 15m / min, heat-sealed quantity 100, 50℃ or 25℃ water standing for 30 minutes, vacuum degree -30kpa, and the detected vacuum leakage rate = number of leaks / total number*100%.

[0075] Sensory test: The composite kraft paper is graded according to its surface smoothness and softness, from 1 to 3, with 1 being the best and 3 being the worst.

[0076] The results are shown in Table 1 below.

[0077] Table 1 Performance test results

[0078]

[0079]

[0080] From the above performance test results, it can be seen that the composite kraft paper of Examples 1-2 has good waterproof and breathable effects, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect of the outer layer, the middle layer and the inner layer.

[0081] However, the comparative examples are significantly worse than the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the ratio of PBAT, PLA, and polylactic acid-glycolic acid copolymer is changed, and it can be seen that the waterproof effect decreases at high temperature. The types of fillers in comparative example 2 are different, and the parameters of fillers in comparative example 3 are different. From the results, it can be seen that the air permeability effect is affected. In comparative example 4, the ratios of thermoplastic polyurethane B and modified thermoplastic polyurethane are different, and thermoplastic polyurethane A in comparative example 5 is not modified. From the results, it can be seen that the tensile effect decreases. In comparative example 6, the models of thermoplastic polyurethane A and thermoplastic polyurethane B are different, and it can be seen that the tensile strength and sensory quality of the composite kraft paper are affected. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0082] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A moisturizing composite kraft paper, characterized in that: It includes an outer layer, a middle layer and an inner layer; the outer layer is made of kraft paper, the middle layer is an adhesive layer, and the inner layer is a modified PBAT film; The preparation method of the modified PBAT film comprises the following steps: by weight, 80-85 parts of PBAT, 7-12 parts of PLA, 15-20 parts of polylactic acid-glycolic acid copolymer and 0.7-1 part of anti-hydrolysis agent are mixed, the temperature is raised to 220-230° C., the stirring speed is 80-90 r / min, the stirring reaction time is 2-3 hours, 5-8 parts of nano fillers are continuously added, ultrasonic dispersion is performed for 15-20 minutes to obtain a mixture, the mixture is added to a cast film machine, cast to obtain a cast film, and calendered using a water-cooled calendering roller with a surface temperature of 20-25° C. to obtain a modified PBAT film.

2. The moisturizing composite kraft paper according to claim 1, characterized in that: The nano filler comprises nano calcium carbonate, nano zinc oxide and nano lanthanum oxide in a weight ratio of 1: (1.2-1.5): (0.6-0.8).

3. The moisturizing composite kraft paper according to claim 2, characterized in that: The particle size of the nano calcium carbonate is 15nm-25nm, and the specific surface area is 30-60m 2 / g, the particle size of nano lanthanum oxide is 30nm-50nm, and the specific surface area is 15-30m 2 / g; the particle size of nano lanthanum oxide is 30nm-50nm, and the specific surface area is 30-50m 2 / g.

4. The moisturizing composite kraft paper according to claim 1, characterized in that: The anti-hydrolysis agent is bis(2,6-diisopropylphenyl)carbodiimide.

5. The moisturizing composite kraft paper according to claim 1, characterized in that: The preparation method of the adhesive layer comprises the following steps: by weight, (1) 15-20 parts of brominated butyl rubber are plasticized at 170-180° C. for 5-10 minutes, and then 0.3-0.5 parts of silane coupling agent KH550, 2-4 parts of magnesium stearate, and 100 parts of thermoplastic polyurethane A are added, and the mixture is mixed for 15-20 minutes, and then crushed at room temperature to obtain a modified thermoplastic polyurethane; (2) 10-14 parts of thermoplastic polyurethane B, 20-25 parts of modified thermoplastic polyurethane, 0.04-0.07 parts of ultraviolet absorber and 0.02-0.05 parts of antioxidant are mixed, and cast by a single screw extruder to obtain a cast film, which is then calendered by a water-cooled calendering roller with a surface temperature of 20-25° C. to obtain an adhesive layer.

6. The moisturizing composite kraft paper according to claim 5, characterized in that: Thermoplastic polyurethane A is thermoplastic polyurethane of model 9670A; thermoplastic polyurethane B is thermoplastic polyurethane of model 9370AU.

7. The moisturizing composite kraft paper according to claim 5, characterized in that: The barrel temperature of the single-screw extruder is 100-105°C in section 1, 130-135°C in section 2, 145-150°C in section 3, 160-165°C in section 4, and 150-155°C in section 5.

8. The moisturizing composite kraft paper according to claim 1, characterized in that: The preparation method of the moisturizing composite kraft paper comprises the following steps: placing the outer layer, the middle layer and the inner layer on a hot roller press in order, stacking them from top to bottom, and hot roller pressing and laminating them to obtain the moisturizing composite kraft paper.

9. The moisturizing composite kraft paper according to claim 8, characterized in that: Rolling temperature is 130-135℃, pressure is 4.5-5kg / cm 2 .

10. The moisturizing composite kraft paper according to claim 1, characterized in that: The thickness of the outer layer is 20-25 μm, the thickness of the inner layer is 10-15 μm, and the thickness of the middle layer is 15-20 μm.

Citation Information

Patent Citations

  • Paper-plastic composite film and production process thereof

    CN101871187A

  • Fully biodegradable composite material

    CN105966014A

  • Degradable kraft paper buffer air cushion film with good waterproofness and preparation method thereof

    CN112522992A

  • Degradable kraft paper buffer air cushion film with good barrier property and preparation method thereof

    CN112553967A

  • Wet-skid-resistant modified thermoplastic polyurethane as well as preparation method and application thereof

    CN114891338A